Highly Oriented Cubic Crystalline Perovskite Thin Film of Methylammonium Lead Bromide - Ayi Bahtiar (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2020)
Organic-inorganic lead halide perovskite materials have been intensively developed for variety optoelectronic applications including solar cells, light-emitting diode and photodetection due to their excellent properties including bandgap tunability, long charge carrier diffusion length, and outstanding optoelectronic merits. Recently, perovskite methylammonium lead bromide (CH3NH3PbBr3 or MAPbBr3) has intensively studied for X-Ray detectors due to high stability against temperature and humidity and also has high X-Ray coefficient attenuation. Most of the perovskite-based optoelectronic devices are using thin films, whose their stability are highly depending on thin film morphology, including grain boundaries and crystal orientation. Morphological control, therefore, plays a significant role to produce high quality perovskite thin films. Thin films perovskite MAPbBr3 were prepared using spin-coating technique at room tempperature with 70% relative humidity. Its absorption spectra was measured using UV-Vis spectroscopy, its crystal structure using X-Ray Diffraction and morphology of thin films using Scanning Electron Microscopy (SEM). The optical bandgap of MAPbBr3 thin film is 2.23 eV derived from its absorption spectrum. The film is very stable against humidity confirmed by unchange of its absorption spectrum after 24 hours stored at room temperature with 70% relative humidity. The film shows cubic crystal structure with lattice constant 5.99 Å and high highly oriented in x-axis. The SEM images show cubic crystallites with size larger than 2 micrometer. The morphology of thin film and crystallite size are influenced by adding ethylammonium iodide additive or anti-solvent chlorobenzene treatment.